ASSESSMENT OF THE LEVEL OF 25-HYDROXYVITAMIN D IN PATIENTS WITH NEWLY DIAGNOSED TYPE 2 DIABETES MELLITUS - Bazarova Sitora Tashpulatovna (KONFERENSIYALAR, 2025)
Abstract:  Vitamin  D  is  a  steroid  prohormone  synthesized  in  the  skin following  UV  exposure  or  else  acquired  by  supplemental  or  dietary  intake. Originally,  it  was  described  as  regulator  of  calcium  homeostasis,  but  has  since been  shown  to  play  a  much  greater,  comprehensive  role  including  protection against  immune  dysfunction,  cancer,  cardiovascular  conditions,  hypertension, metabolic  syndrome  (MS)  and  diabetes.  The  role  of  vitamin  D  in  modulating metabolic  processes  is  increasingly  recognized,  with  emerging  evidence suggesting a link between vitamin D deficiency and the pathogenesis of Type II Diabetes Mellitus (T2DM). Given the high prevalence of both conditions globally, understanding this relationship could have significant clinical implications. This study seeks to investigate the prevalence of vitamin D deficiency among newly diagnosed  T2DM  patients  and  its  potential  impact  on  managing  the  disease effectively.